A novel oncolytic vaccinia virus with multiple gene modifications involved in viral replication and maturation increases safety for intravenous administration while maintaining proliferative potential in cancer cells. - Go Okita; Kiyotaka Suenaga; Masashi Sakaguchi; Toshio Murakami (PLoS ONE)
To generate a novel oncolytic vaccinia virus with improved safety and productivity, the genome of smallpox vaccine strain LC16m8 was modified by a bacterial artificial chromosome system. By using LC16m8, a replicating virus homologous to the target virus, as a helper virus for the bacterial artificial chromosome system, we successfully recovered genome-edited infectious viruses. Oncolytic viruses with limited growth in normal cells were obtained by deleting the genes for vaccinia virus growth factor (VGF), extracellular signal-regulated kinase-activating protein (O1L), and ribonucleotide reductase (RNR) present in the viral genome. Furthermore, the amino acid residues of seven proteins involved in extracellular enveloped virus virion formation were replaced to the IHD-J strain sequence, which is known to highly express extracellular enveloped virus. In cultured cancer cells (HeLa), these modified viruses showed cytotoxicity and increased productivity, but it was confirmed that the cytotoxicity was suppressed in normal cells (normal human dermal fibroblasts). For in vivo safety evaluation, a modified virus (MD-RVV-ΔRR-EEV6) in which the VGF, O1L, and RNR genes of LC16m8 were deleted and the genes of six extracellular enveloped virus-associated proteins were replaced with sequences derived from IHD-J strain, and another modified virus (MD-RVV) lacking only the VGF and O1L were administered intravenously to severe combined immunodeficiency mice. In the MD-RVV administration, animals in all dose groups died by 40 days after virus administration. On the other hand, after MD-RVV-ΔRR-EEV6 administration, 3 out of 5 animals in the high and medium dose groups and all animals in the low dose group were still alive by day 71, the end of the observation period. These results demonstrate that genome editing of oncolytic vaccinia virus can delete genes involved in viral replication to improve safety in normal cells, while replacing genes involved in maturation improves proliferative potential in cancer cells.